Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find the composition [tex]\((g \circ f \circ h)(x)\)[/tex], we need to apply each function successively. Let's break it down step-by-step.
### Step 1: Define the functions
We have three functions given:
- [tex]\( f(x) = 3x - 1 \)[/tex]
- [tex]\( g(x) = x^3 \)[/tex]
- [tex]\( h(x) = x \)[/tex] (Assuming [tex]\( h(x) = x \)[/tex] as it is not provided explicitly)
### Step 2: Compose [tex]\( f \)[/tex] and [tex]\( h \)[/tex]
First, we need to find [tex]\( f(h(x)) \)[/tex]:
[tex]\[ f(h(x)) = f(x) \][/tex]
[tex]\[ f(x) = 3x - 1 \][/tex]
So,
[tex]\[ f(h(x)) = 3x - 1 \][/tex]
### Step 3: Compose [tex]\( g \)[/tex] and [tex]\( f(h(x)) \)[/tex]
Next, we need to find [tex]\( g(f(h(x))) \)[/tex]:
[tex]\[ g(y) = y^3 \][/tex]
where [tex]\( y = f(h(x)) \)[/tex].
From Step 2, we know:
[tex]\[ f(h(x)) = 3x - 1 \][/tex]
Thus,
[tex]\[ g(f(h(x))) = g(3x - 1) \][/tex]
[tex]\[ g(3x - 1) = (3x - 1)^3 \][/tex]
### Final Result
Combining all the steps, we get:
[tex]\[ (g \circ f \circ h)(x) = (3x - 1)^3 \][/tex]
Hence, the composed function [tex]\((g \circ f \circ h)(x) \)[/tex] is:
[tex]\[ (g \circ f \circ h)(x) = (3x - 1)^3 \][/tex]
### Step 1: Define the functions
We have three functions given:
- [tex]\( f(x) = 3x - 1 \)[/tex]
- [tex]\( g(x) = x^3 \)[/tex]
- [tex]\( h(x) = x \)[/tex] (Assuming [tex]\( h(x) = x \)[/tex] as it is not provided explicitly)
### Step 2: Compose [tex]\( f \)[/tex] and [tex]\( h \)[/tex]
First, we need to find [tex]\( f(h(x)) \)[/tex]:
[tex]\[ f(h(x)) = f(x) \][/tex]
[tex]\[ f(x) = 3x - 1 \][/tex]
So,
[tex]\[ f(h(x)) = 3x - 1 \][/tex]
### Step 3: Compose [tex]\( g \)[/tex] and [tex]\( f(h(x)) \)[/tex]
Next, we need to find [tex]\( g(f(h(x))) \)[/tex]:
[tex]\[ g(y) = y^3 \][/tex]
where [tex]\( y = f(h(x)) \)[/tex].
From Step 2, we know:
[tex]\[ f(h(x)) = 3x - 1 \][/tex]
Thus,
[tex]\[ g(f(h(x))) = g(3x - 1) \][/tex]
[tex]\[ g(3x - 1) = (3x - 1)^3 \][/tex]
### Final Result
Combining all the steps, we get:
[tex]\[ (g \circ f \circ h)(x) = (3x - 1)^3 \][/tex]
Hence, the composed function [tex]\((g \circ f \circ h)(x) \)[/tex] is:
[tex]\[ (g \circ f \circ h)(x) = (3x - 1)^3 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.